A Direct Synthesis of 2‐(ω‐Carboxyalkyl)isoflavones from ortho‐Hydroxylated Deoxybenzoins. Issue 39 (11th October 2018) - Mrug, Galyna P.; Demydchuk, Bohdan A.; Bondarenko, Svitlana P.; Sviripa, Vitaliy M.; Wyrebek, Przemyslaw; Mohler, James L.; Fiandalo, Michael V.; Liu, Chunming; Frasinyuk, Mykhaylo S.; Watt, David S.
Abstract : As part of a program focused on the development of new antineoplastic agents based on scaffolds found in natural products, we explored the isoflavone family as potential enzyme inhibitors. We required biotin‐modified isoflavones to identify potential biological targets, and we selected the C‐2 position in isoflavones as an attachment site for an alkyl group bearing a terminal carboxylic acid to which we could attach a biotin derivative. The base‐catalyzed condensation of 2, 4‐dihydroxy‐substituted deoxybenzoins with cyclic anhydrides mediated by a combination of triethylamine and 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene led to an efficient synthesis of the desired 2‐(ω‐carboxyalkyl)isoflavones with functional groups at C‐5, 6 and 7 and with various substituents in the C‐3 phenyl group. Abstract : The base‐catalyzed chromone ring‐closure reaction was developed for one‐step synthesis of various 2‐(ω‐carboxyalkyl)isoflavones bearing electron‐donating and electron‐withdrawing groups.